The Comet - (:unkn) unknown (Cornell, Thomas, 1789)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Comets; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons